945 Are Extended Criteria Donor Kidneys from 70 years-old and above Good Enough to Accept? A Single Centre Experience. (19th August 2022) - Khudr, J; Sharma, H; Ridgway, D; Hammad, A; Elmghrbee, A
Abstract: Aim: As a result of increasing demand in recent years in organ donation and transplantation, the transplant community has been utilizing organs previously considered unsuitable for transplantation, including organs from extended criteria donors (ECD) and donors after circulatory arrest (DCD). This has led to higher rates of non-functioning and poorer outcomes, increasing the uncertainty when to accept or decline a donor organ. Our objective is to measure patient and graft outcomes of kidney transplants from ECDs aged 70 years and older. Method: A retrospective study of 104 renal transplanted patients from ECDs between April 2010 and March 2014. Recipients referred to other centres were excluded from the study. Follow-up period was 7 years. Results: At 7 years follow up, graft survival among recipients from ECDs older were 42.5%(n=17/40) while from ECDs younger were 58% (n=37/64) (P = 0.1594). Death censored graft survival (patient died with functioning graft ). ECDs older death censored graft survival was 80% (n=32/40) and 82.8% (n=53/64) for ECDs younger (P = 0.7963). Patient survival: 70.3% of recipients from ECDs younger and 60% of recipients from ECDs older were alive at seven years post-transplant. (P = 0.2945). Conclusions: There was no significant difference between the two cohorts in graft and patient survival. The use of kidneys from donors aged ≥70 years has yielded generally satisfactory results when compared to younger ECDs 50–69 years old donors.